Immigration and Majority Voting on Income Redistriubtion - Is there a Case for Opposition from Natives? - Karin Mayr (Johannes Kepler University of Linz, Department of Economics, 2003)
This paper examines the effect of immigration on the level of income redistribution via majority voting on the income tax. As a main result, we derive multiple tax equilibria if immigrants are allowed to vote and the skill composition of natives is not too homogeneous. In this case, the outcome of a native referendum on giving immigrants the right to vote would be negative, since immigrants could overthrow the native majority and change the tax rate that is utility-maximising for natives. It is found that at best, natives are indifferent towards immigrant voting, and the outcome of a corresponding referendum would be indeterminate.
Keywords: F22; H73; D72; 330; Political Economy; Immigration; Income Redistribution; Einwanderung; Einkommensteuer; Abstimmungsregel; Theorie